THE DYNAMICS OF APPLYING BOTH ISLAMIC AND CONVENTIONAL LAW IN THE INHERITANCE OF BANCEAUY CUSTOMARY VILLAGE - Kusmayanti, Hazar; Suwandono, Agus (Jurnal Al-Dustur, 2024)
Due to the existence of three distinct systems of inheritance law—civil heirship law, Islamic inheritor ship law, and customary inherited law—Indonesian inheritance law is still pluralistic. There are parallels and variances among the components of inheritance law because there are variations in the legal system governing such inheritance. Finding out how inheritance disputes are resolved in Banceuy Customary Village in relation to Islamic law is the aim of this study. This normative research approach employs descriptive analytical research specifications, which involve describing, analyzing, and putting into practice the relevant legal laws. Research indicates that, even though the indigenous communities in the Banceuy district of Subang are Islamic, the law of parental inheritance appears to apply to the indigenous village. However, the division of inherits appears to be dependent on the affinity system in place, as the group of heirs equally accounted for the relationship of relativity through the male and female lines. This division of inheritance falls under the category of the receptie theory, which was abandoned but held that Muslims are subject to Islamic law if it is accepted or mandated by customary law. The concept of equal inheritance division in the indigenous village of Banceuy, if linked to Islamic law, the author claims, originated from a cooperative agreement that was carried out successively so that it became a customary practice that was initially a disclaimer for the implementation of division of heritage religiously or disclaimed.